Earnings, regulatory capital, and tax management: Comments - Shackelford, Douglas A. (Journal of Accounting and Economics, 1996)
In the preceding papers, Beaver and Engel and Adiel investigate managerial discretion in the financial services industry. This comment evaluates the contribution and limitations of both papers and suggests avenues for further extensions.